Perception of People Living with HIV and Healthcare Workers on Differentiated Service Delivery Programs in Nigeria: A Qualitative Study - Johnbaptist Ezenduka; Peter Nwaokennaya; Gbenga Benjamin Obasa; Geoffrey Ogbeke; Ogonna Onuorah; Lawal Abubakar; Adebobola Bashorun; Ginigeme Ogochukwu; Emerenini Franklin; Adewale Akinjeji (PLoS ONE, 2025)
Nigeria, home to approximately 1.9 million people living with HIV (PLHIV), faces significant challenges in providing adequate care and treatment to the teeming number of PLHIV, particularly following the adoption of the ‘test and treat’ policy and the HIV ‘SURGE’ initiative. The Differentiated Service Delivery (DSD) model was introduced to address the increased burden on the healthcare system, offering patient-centered care through diverse methods like community-based care, fast-track drug refills, and task-shifting to lower-level healthcare providers. This study, conducted by the National AIDS and STI Control Program (NASCP) in collaboration with ICAP at Columbia University, evaluates the perspectives of healthcare workers and PLHIV on DSD programs in Nigeria. This is a qualitative study involving key informant interviews (KIIs) with 12 healthcare workers and focus group discussions (FGDs) with 153 PLHIV across four Nigerian states (Anambra, Kaduna, Lagos, Taraba). Healthcare workers with at least one year of ART service experience and PLHIV on ART for at least one year with suppressed viral loads were included in the study. Data was analyzed using an inductive, thematic approach to identify emergent patterns and themes. The study revealed that DSD models, such as peer-led Facility ART groups and community pharmacy ART refills, were widely implemented. The primary factors influencing the deployment of DSD models included client convenience and the need to alleviate healthcare worker load. Positive experiences with DSD were associated with convenience, confidentiality, and affordability, whereas negative perceptions stemmed from high service costs, poor healthcare worker attitudes, and confidentiality concerns. Additionally, the study highlighted the necessity for continuous training of healthcare workers, engagement with PLHIV, and increased awareness programs to improve DSD service delivery. Overall, the study underscores the importance of addressing financial barriers, enhancing healthcare worker training, and ensuring confidentiality in optimizing DSD models and improving HIV care outcomes in Nigeria.